Effect of transdermal drug delivery therapy on anxiety symptoms in schizophrenic patients - Zhu, Cuifang; Wang, Xin-Yue; Zhao, Jing; Long, Bin; Xiao, Xudong; Pan, Ling-Yi; Yuan, Ti-Fei; Chen, Jian-Hua (Frontiers in Neuroscience, 2023)
Objective To evaluate the efficacy and safety of transdermal drug delivery therapy for schizophrenia with anxiety symptoms. Methods Eighty schizophrenic patients accompanying anxiety disorders were randomly assigned to the treatment group (n=40) and the control group (n=40) with 6 weeks of follow-up. Patients in the treatment group were treated with the original antipsychotic drug program and were additionally treated with Chinese medicine targeted penetration therapy. Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD-17), and treatment emergent symptom scale (TESS) were evaluated before enrollment, 3 weeks, and 6 weeks after treatment. Positive and Negative Symptom Scale (PANSS) was assessed at baseline and 6 weeks. Results After 3 and 6 weeks treatments, the scores of HAMA scale in the treatment group were lower than those in the control group (P < 0.001). Neither HAMD-17 scale scores, PANSS total scores nor subscale scores were significantly different between the two groups (P>0.05), and no significant differences were detected in adverse effects that occurred during the intervention between the two groups (P>0.05). After 6 weeks of penetration therapy, there was a low negative correlation between total disease duration and the change in HAMA scale score (pre-treatment-post-treatment) in the treatment group. Conclusion Combined traditional Chinese medicine directed penetration therapy can improve the anxiety symptoms of schizophrenia patients with a safe profile.